The animated still life. Ingrid Vang Nyman's use of self-contradictory spatial order in Pippi Longstocking - Elina Druker (Barnboken: Tidskrift för Barnlitteraturforskning, 2011)
Ingrid Vang Nyman’s illustrations to Astrid Lindgren’s books about Pippi Longstocking seem to contradict customary perspective logic. In her interior images, Vang Nyman displays curiously assorted objects, animate and inanimate, in a range of textures, colours and shapes. The elements in her compositions are often presented at tipped angles, where everything is observed without overlapping perspectives. Why this constant defiance of gravity, the free distortion of proportions and multiplicity of details? Everything seems to be in motion, in a state of flux and turmoil, pointing to the adventurous potential of everyday places and objects. In this paper, I discuss Ingrid Vang Nyman’s use of pictorial effects and her way of playing with perspective and spatial order, and I will place this technique in the larger context of art history.